Patterns of Sedation Weaning in Critically Ill Children Recovering From Acute Respiratory Failure*. Issue 1 (January 2016) - Best, Kaitlin M.; Asaro, Lisa A.; Franck, Linda S.; Wypij, David; Curley, Martha A. Q.
Abstract : Objective: To characterize sedation weaning patterns in typical practice settings among children recovering from critical illness. Design: A descriptive secondary analysis of data that were prospectively collected during the prerandomization phase (January to July 2009) of a clinical trial of sedation management. Setting: Twenty-two PICUs across the United States. Patients: The sample included 145 patients, aged 2 weeks to 17 years, mechanically ventilated for acute respiratory failure who received at least five consecutive days of opioid exposure. Interventions: None. Measurements and Main Results: Group comparisons were made between patients with an intermittent weaning pattern, defined as a 20% or greater increase in daily opioid dose after the start of weaning, and the remaining patients defined as having a steady weaning pattern. Demographic and clinical characteristics, tolerance to sedatives, and iatrogenic withdrawal symptoms were evaluated. Sixty-six patients (46%) were intermittently weaned; 79 patients were steadily weaned. Prior to weaning, intermittently weaned patients received higher peak and cumulative doses and longer exposures to opioids and benzodiazepines, demonstrated more sedative tolerance (58% vs 41%), and received more chloral hydrate and barbiturates compared with steadily weaned patients. During weaning, intermittently weaned patients assessed for withdrawal had a higher incidence of Withdrawal Assessment Tool-version 1 scores of greater than or equal to 3 (85% vs 46%) and received more sedative classes compared with steadily weaned patients. Conclusions: This study characterizes sedative administration practices for pediatric patients prior to and during weaning from sedation after critical illness. It provides a novel methodology for describing weaning in an at-risk pediatric population that may be helpful in future research on weaning strategies to prevent iatrogenic withdrawal syndrome.